Safe and durable antifouling blade, scissors and art knife

By using aqueous prereacting compositions to form a three-dimensional network structure and introducing nanoscale silica on the surface of the blade, the existing antifouling coatings have been solved and the potential problems of organic fluorine compounds under mechanical wear are achieved. Safe and durable anti-fouling coating with high transparency, mechanical durability and excellent anti-fouling performance.

CN119391297APending Publication Date: 2025-02-07SHANGHAI M&G STATIONERY INC

Patent Information

Application Number
CN202411669138.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-07

AI Technical Summary

Technical Problem

The existing antifouling coating is easy to decompose under mechanical wear, resulting in the loss of liquid repellency, and the high cost of organic fluorine compounds, bioaccumulation and potential toxicity. The high density and poor flexibility of polymer antifouling coatings limit their application. field.

Method used

The addition reaction of the aqueous electron-supply prereaction composition and the aqueous electron-supply prereaction monomer to form a solid three-dimensional network structure, and the nano-scale silica is introduced through inorganic-organic combination to prepare excellent mechanical properties and protection Sticky, corrosion-resistant safe and durable anti-fouling coating.

Benefits of technology

It achieves high transparency, mechanical durability and excellent anti-fouling performance of the coating, avoids the use of organic solvents and coating VOC emissions, meets environmental protection requirements, and improves the safety and service life of the product.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119391297A_ABST
    Figure CN119391297A_ABST
Patent Text Reader

Abstract

The invention provides a safe and durable blade, the surface of the blade is provided with a safe and durable coating, the safe and durable coating comprises a water-based electron-donating pre-reaction composition and a water-based electron-accepting pre-reaction monomer, and the water-based electron-donating pre-reaction composition and the water-based electron-accepting pre-reaction monomer are subjected to an addition reaction to form a firm three-dimensional network structure. The safe and durable blade with excellent mechanical property, adhesion resistance and corrosion resistance is prepared; in the preparation process, the A component and the B component are prefabricated in an aqueous emulsion manner, so that the use of organic solvents is reduced, the raw materials meet the national environmental protection requirements, the VOC emission of the coating is reduced, the safety of the product in the manufacturing, transportation and use processes is enhanced, the national policy requirements are met, and the consciousness of enterprises on environmental protection and safe production is promoted; the invention further provides a pair of safe and durable scissors and an art knife.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This patent relates to the field of stationery, and in particular to a safe, durable and anti-fouling blade, scissors and utility knife. Background Art

[0002] The coating exhibits excellent repellency against water-based and oil-based pollutants, and forms movable droplets that slide without leaving any traces. It is ideal in many fields such as self-cleaning, chemical shielding, anti-fouling, anti-graffiti, and bacterial prevention. For metal-based products, the coating is usually applied in the back-end process of its processing to protect the structural stability of the metal substrate. Therefore, it is necessary to develop a coating with excellent anti-corrosion and anti-fouling capabilities. Spraying coatings on the surface of scissors, utility knives and other knives plays an anti-corrosion and anti-sticking protective role. The commonly used method is to spray Teflon coatings.

[0003] Currently, there are four main methods to create antifouling surfaces. The first technique is based on the lotus effect phenomenon. By controlling the roughness of the substrate and adding an appropriate amount of hydrophobic lubricating material, a super-amphiphobic coating with microscale reentrant or double reentrant characteristics and low surface energy is prepared. However, the rough surface of this coating not only reduces its own transparency, but also is susceptible to mechanical wear, resulting in a decrease in fluid displacement performance. Another method to construct an antifouling surface is to use a low surface tension liquid to simulate the common flower and grass design porous surface, lubricate the porous surface, and form a smooth liquid-injected porous surface. Compared with the super-amphiphobic coating, the liquid on the porous surface has a lower contact angle, but a lower hysteresis, better elasticity to external pressure, and higher optical transparency. However, the unbounded lubricant injected into the porous surface may be exhausted due to leakage, evaporation or other reasons, resulting in a deterioration of the antifouling performance. The third alternative strategy is to graft a polymer with low surface energy onto a pretreated flat substrate to form a liquid-like monolayer surface. Compared with the porous surface, the hydrophobic polymer is covalently bonded to the flat substrate, which can effectively avoid the degradation of antifouling performance due to the exhaustion of the lubricant. However, this monolayer is easily decomposed under mechanical wear, resulting in the loss of liquid repellency. On this basis, smooth polymer-based antifouling coatings have begun to be developed by grafting silicone or organic fluorine into a polymer matrix. In contrast, this coating exhibits the advantages of high transparency and mechanical durability, and does not require the substrate to be treated, successfully overcoming the potential problems of the above-mentioned antifouling surface. However, due to the disadvantages of high cost, bioaccumulation and potential toxicity, the application range of organofluorine compounds is tending to decrease. What is more serious is that the polymer antifouling coating itself has an extremely high density and poor flexibility, which further limits its application areas.

[0004] Spraying Teflon coating on the surface of scissors, utility knives and other knives has multiple functions, which are mainly derived from the unique properties of Teflon coating. First, Teflon coating has excellent chemical inertness and can effectively resist the erosion of chemical substances such as acids, alkalis and salts, thereby protecting the surface of scissors and utility knives from corrosion and extending the service life of scissors, utility knives and other knives. Second, it provides metal wear resistance. Teflon coating also has high wear resistance, which can effectively protect the blade from wear during the use of scissors, maintain the sharpness and service life of scissors. This is especially important for users who need to use scissors frequently for shearing operations. Third, it has anti-stick properties. As the originator of non-stick coating, Teflon coating also has outstanding anti-stick properties. After being applied to the surface of scissors, utility knives and other knives, it can effectively reduce the situation of scissors adhering to sticky substances such as tape and glue during use, making the knives easier to clean and maintain. However, the production process of Teflon coating may involve some chemicals that are harmful to the human body and the environment, such as perfluorooctanoic acid (PFOA) and perfluorooctane sulfonyl compounds (PFOS). These substances may decompose and release harmful substances at high temperatures, posing a potential threat to human health and the environment. Therefore, it is urgent to choose a non-stick coating to replace Teflon coating for use in scissors and other stationery knife industries. Summary of the invention

[0005] In order to improve the antifouling and wear resistance of the blade surface, and to prepare safe, durable and antifouling scissors and utility knives, this patent provides the following technical solutions:

[0006] The first aspect: provides a safe, durable and anti-fouling blade, which has a safe, durable anti-fouling coating on the surface of the blade substrate. The safe, durable anti-fouling coating is a three-dimensional network structure, and the safe, durable anti-fouling coating is formed by the polymerization reaction of the following components: an aqueous electron-donating pre-reaction composition; an aqueous electron-accepting pre-reaction monomer; gas-phase silica; an additive; and water.

[0007] Furthermore, the aqueous electron donating pre-reaction composition includes a first aqueous electron donating pre-reaction monomer and a second aqueous electron donating pre-reaction monomer; the first aqueous electron donating pre-reaction monomer is one or more selected from MT silicone resin, MQ silicone resin, MDT silicone resin, and MTQ silicone resin; the second aqueous electron donating pre-reaction monomer includes vinyl silicone oil; and the aqueous electron accepting pre-reaction monomer includes hydrogen-containing silicone oil.

[0008] Furthermore, the vinyl content of the first aqueous electron-donating pre-reaction monomer is 0.09-0.10 mol / 100g, 0.10-0.11 mol / 100g or 0.11-0.12 mol / 100g; the vinyl content of the second aqueous electron-donating pre-reaction monomer is 0.02-0.05 mol / 100g, 0.05-0.08 mol / 100g or 0.08-0.11 mol / 100g; the hydrogen content of the aqueous electron-accepting pre-reaction monomer is 0.30-0.32%, 0.32-0.34%, 0.34-0.36%, 0.36-0.38% or 0.38-0.40%.

[0009] Furthermore, the components of the safe and durable antifouling coating include, by weight: 3 to 5 parts, 5 to 7 parts, 7 to 9 parts, 9 to 11 parts or 11 to 13 parts of the first aqueous electron-donating pre-reaction monomer; 28 to 30 parts, 30 to 32 parts, 32 to 34 parts, 34 to 36 parts or 36 to 38 parts of the second aqueous electron-donating pre-reaction monomer; 34 to 36 parts, 36 to 38 parts, 38 to 40 parts, 40 to 42 parts of the aqueous electron-accepting pre-reaction monomer or 42 to 44 parts; the weight fraction ratio of the aqueous electron accepting pre-reaction monomer composition to the aqueous electron donating pre-reaction is 0.83 to 0.86, 0.86 to 0.89, 0.89 to 0.92, 0.92 to 0.95, 0.95 to 0.98, 0.98 to 1.01, 1.01 to 1.03, 1.03 to 1.05, 1.05 to 1.08, 1.08 to 1.11 or 1.11 to 1.14.

[0010] Furthermore, the safe and durable coating is prepared by the following steps: S1: preparing an emulsion A containing an aqueous electron-accepting pre-reaction monomer, and preparing an emulsion B containing a first aqueous electron-donating pre-reaction monomer and a second aqueous electron-donating pre-reaction monomer; S2: mixing the emulsion A and the emulsion B evenly and spraying them onto a blade substrate; S3: allowing the blade substrate to stand and undergo a polymerization reaction to obtain a safe, durable and antifouling blade with a safe and durable antifouling coating.

[0011] Furthermore, emulsion A includes hydrogenated silicone oil, fumed silica and a first emulsifier; the first emulsifier is a composite emulsifier comprising nonionic and polymeric types; emulsion B includes vinyl silicone oil, MQ resin, a second emulsifier, a catalyst, a film-forming aid, a wetting agent and a rust inhibitor; the catalyst is a chloroplatinic acid catalyst; the film-forming aid is an alcohol ether compound; the film-forming aid includes ethylene glycol monobutyl ether and / or diethylene glycol butyl ether; the second emulsifier is a composite emulsifier comprising nonionic and polymeric types; the wetting agent is an organosilicon wetting agent; and the rust inhibitor is one or two selected from aluminum tripolyphosphate and zinc phosphate.

[0012] Furthermore, the polymerization reaction temperature is 171-175°C, 175-179°C, 179-183°C, 183-187°C or 187-191°C; the polymerization reaction time is 10-12min, 12-14min, 14-16min, 16-18min or 18-20min.

[0013] Furthermore, the additives include emulsifiers, catalysts, film-forming aids, wetting agents and rust removers.

[0014] A second aspect: provides a pair of safe, durable and anti-fouling scissors, the scissors comprising the above-mentioned safe, durable and anti-fouling blades.

[0015] A third aspect: A safe, durable and anti-fouling utility knife is provided, the utility knife comprising the safe, durable and anti-fouling blade mentioned above.

[0016] This patent has the following beneficial effects:

[0017] 1. This patent discloses a safe, durable and antifouling blade. The blade surface has a safe, durable and antifouling coating. The safe, durable and antifouling coating includes an aqueous electron-donating pre-reaction composition and an aqueous electron-accepting pre-reaction monomer. The aqueous electron-donating pre-reaction composition and the aqueous electron-accepting pre-reaction monomer undergo an addition reaction to form a strong three-dimensional network structure. Nano-scale silica is introduced into the coating through an inorganic-organic combination to prepare a safe, durable and antifouling blade with excellent mechanical properties, anti-sticking and anti-corrosion.

[0018] 2. During the preparation process, the two components A / B are prefabricated in the form of water emulsion, which reduces the use of organic solvents, meets the national environmental protection requirements in terms of raw materials, reduces the VOC emissions of coatings, and enhances the safety of products during manufacturing, transportation, and use. This not only complies with national policy requirements, but also promotes the awareness of enterprises to pay attention to environmental protection and safe production. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] In order to more clearly illustrate the technical solution of the embodiment of this patent, the following is a brief introduction to the drawings required for use in the embodiment. It should be understood that the following drawings only show certain embodiments of this patent and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other relevant drawings can be obtained based on these drawings without creative work.

[0020] Figure 1 This is a process flow chart for preparing Example 1 of this patent. DETAILED DESCRIPTION

[0021] The detailed features and advantages of this patent are described in detail in the specific implementation method below, and the content is sufficient to enable any technical personnel in this field to understand the technical content of this patent and implement it accordingly. According to the description, claims and drawings disclosed in this specification, technical personnel in this field can easily understand the relevant purposes and advantages of this patent.

[0022] The terms used in this patent are for the purpose of describing specific embodiments only and are not intended to limit this patent. The singular forms "a", "the" and "the" used in this patent and the appended claims are also intended to include plural forms unless the context clearly indicates otherwise. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.

[0023] It should be understood that although the terms "first", "second", "third", etc. may be used in this patent to describe various information, this information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of this patent, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this patent, "multiple" means two or more, unless otherwise clearly and specifically defined.

[0024] Scissors and utility knives are commonly used tools in the field of stationery. Scissors are usually composed of a rotor part, a stator part and a rivet, wherein the rotor part is composed of a rotor shear ("rotating blade") and a rotor handle ("rotating handle"), and the stator part is composed of a stator shear ("stator blade") and a stator handle ("fixed handle"). The rotor shear and the stator shear are sharp blades arranged crosswise to cut objects, and the rotor handle and the stator handle are made of plastic to provide a comfortable grip. The blade body is stainless steel cut into an appropriate shape, and is forged into a blade with high hardness through a mold and a large hydraulic press, and the forged blade is ground and polished, and finally a layer of anti-corrosion, non-stick protective coating is sprayed on the outer surface of the blade to increase the service life of the blade.

[0025] Utility knives usually consist of a sharp blade and a grip. The blade body is made of stainless steel and the grip is made of polyester resin or plastic. The blade body is cut into an initial shape and then ground to obtain a certain shape and contour. The blade is then calcined to increase the hardness and wear resistance of the blade, quenched to increase toughness and elasticity, and finally a layer of anti-corrosion, non-stick protective coating is sprayed on the outer surface of the blade to increase the service life of the blade.

[0026] The invention discloses a safe and durable blade, which is suitable for tools realizing cutting and chopping functions in the field of stationery, including but not limited to scissors and utility knives.

[0027] The raw materials, specifications and sources used in the following examples are shown in Table 1:

[0028] Table 1 Raw material names and purchasing manufacturers

[0029]

[0030]

[0031] Example 1

[0032] A safe and durable coating, the preparation raw materials of which are as follows: 40 parts of hydrogen silicone oil, 30 parts of vinyl silicone oil, 8 parts of MQ resin, 0.1 parts of catalyst (chloroplatinic acid), 8 parts of non-ionic emulsifier (Tween80), 8 parts of non-ionic emulsifier (Span80), 2 parts of non-ionic emulsifier (OP-10), 2 parts of non-ionic emulsifier (EO-PO), 1 part of film-forming aid (ethylene glycol monobutyl ether), 4 parts of film-forming aid (diethylene glycol butyl ether), 1 part of fumed silica, 0.2 parts of wetting agent, 10 parts of rust inhibitor (aluminum tripolyphosphate), and the remaining solvent is deionized water.

[0033] like Figure 1 As shown, the preparation steps of emulsion A are as follows: 40 parts of hydrogenated silicone oil are added into a beaker, deionized water is added for stirring, a dispersion disk is used for the stirring paddle, 1 part of fumed silica is added during the stirring process, 10 parts of emulsifier are added after stirring evenly, and the mixture is stirred at 2500r / min for 60min, and the sample is taken out after the emulsification is complete;

[0034] Preparation steps of emulsion B: add 30 parts of vinyl silicone oil into a beaker, add deionized water and stir, use a dispersion disk as a stirring paddle, add 8 parts of MQ resin during the stirring process, stir evenly, add 10 parts of emulsifier, 0.1 parts of catalyst, 5 parts of film-forming aid, 0.2 parts of wetting agent, 10 parts of rust inhibitor, stir at 2500r / min for 60min, take out and load the sample;

[0035] Before use, add A / B solution in a ratio of 1:1 and stir quickly to mix evenly, then spray immediately (no more than 30 minutes);

[0036] A emulsion uses Tween80: Span80: OP-10 = 5:3:2 emulsifiers;

[0037] Emulsion B uses Tween80: Span80: EO-PO = 3:5:2 emulsifier compound;

[0038] Ethylene glycol monobutyl ether: diethylene glycol butyl ether = 1:4 is a film-forming aid;

[0039] The wetting agent is a silicone twin structure surfactant (TEGO-4100);

[0040] The catalyst is chloroplatinic acid catalyst;

[0041] The rust inhibitor is aluminum tripolyphosphate;

[0042] The prepared safe and durable coating was sprayed on the polished tinplate with a film thickness of 200 microns, placed in a high-temperature oven for cross-linking and curing, and after completion, taken out and cured for seven days before testing the application performance.

[0043] Example 2

[0044] A safe and durable coating, compared with the previous embodiment, the main raw materials remain unchanged, and the raw material parts and the types of auxiliary agents used are different. The raw materials for its preparation are as follows: 40 parts of hydrogen silicone oil, 30 parts of vinyl silicone oil, 10 parts of MQ resin, 0.1 parts of catalyst (chloroplatinic acid), 8 parts of non-ionic emulsifier (Tween80), 8 parts of non-ionic emulsifier (Span80), 2 parts of non-ionic emulsifier (OP-10), 2 parts of non-ionic emulsifier (EO-PO), 1 part of film-forming aid (ethylene glycol monobutyl ether), 4 parts of film-forming aid (diethylene glycol butyl ether), 1 part of fumed silica, 0.2 parts of wetting agent, and 10 parts of rust inhibitor (zinc phosphate).

[0045] Preparation steps of emulsion A: add 40 parts of hydrogenated silicone oil into a beaker, add deionized water and stir, use a dispersion disk as a stirring paddle, add 1 part of fumed silica during the stirring process, stir evenly, add 10 parts of emulsifier, stir at 2500r / min for 60min, and take out the sample;

[0046] Preparation steps of emulsion B: add 30 parts of vinyl silicone oil into a beaker, add deionized water and stir, use a dispersion disk as a stirring paddle, add 10 parts of MQ resin during the stirring process, stir evenly, add 10 parts of emulsifier, 0.1 parts of catalyst, 5 parts of film-forming aid, 0.2 parts of wetting agent, 10 parts of rust inhibitor, stir at 2500r / min for 60min, take out and load the sample;

[0047] Before use, add A / B solution in a ratio of 1:1 and stir quickly to mix evenly, then spray immediately (no more than 30 minutes);

[0048] The catalyst is chloroplatinic acid catalyst;

[0049] A emulsion uses Tween80: Span80: OP-10 = 5:3:2 emulsifiers;

[0050] Emulsion B uses Tween80: Span80: EO-PO = 3:5:2 emulsifier compound;

[0051] The film-forming aid is ethylene glycol monobutyl ether: diethylene glycol butyl ether = 1:4;

[0052] The wetting agent is a silicone twin structure surfactant (TEGO-4100): polyether siloxane copolymer (TEGO-410) = 3:2;

[0053] The rust inhibitor is zinc phosphate;

[0054] The prepared water-based silicone coating was sprayed on the polished tinplate with a film thickness of 200 microns, placed in a high-temperature oven for cross-linking and curing, and after completion, taken out and cured for seven days before testing the application performance.

[0055] Example 3

[0056] A safe and durable coating, compared with the previous embodiment, the main raw materials remain unchanged, and the number of raw materials and the types of auxiliary agents used are different. The raw materials for its preparation are as follows: 40 parts of hydrogen silicone oil, 34 parts of vinyl silicone oil, 8 parts of MQ resin, 0.1 parts of catalyst (chloroplatinic acid), 8 parts of non-ionic emulsifier (Tween80), 8 parts of non-ionic emulsifier (Span80), 2 parts of non-ionic emulsifier (OP-10), 2 parts of non-ionic emulsifier (EO-PO), 1 part of film-forming aid (ethylene glycol monobutyl ether), 4 parts of film-forming aid (diethylene glycol butyl ether), 1 part of fumed silica, 0.2 parts of wetting agent, 5 parts of rust inhibitor (zinc phosphate), and 5 parts of rust inhibitor (aluminum tripolyphosphate).

[0057] Preparation steps of emulsion A: add 40 parts of hydrogenated silicone oil into a beaker, add deionized water and stir, use a dispersion disk as a stirring paddle, add 1 part of fumed silica during the stirring process, stir evenly, add 10 parts of emulsifier, stir at 2500r / min for 60min, and take out the sample;

[0058] Preparation steps of emulsion B: add 34 parts of vinyl silicone oil into a beaker, add deionized water and stir, use a dispersion disk as a stirring paddle, add 8 parts of MQ resin during the stirring process, stir evenly, add 10 parts of emulsifier, 0.1 parts of catalyst, 5 parts of film-forming aid, 0.2 parts of wetting agent, 10 parts of rust inhibitor, stir at 2500r / min for 60min, take out and load the sample;

[0059] Before use, add A / B solution in a ratio of 1:1 and stir quickly to mix evenly, then spray immediately (no more than 30 minutes);

[0060] The catalyst is chloroplatinic acid catalyst;

[0061] A emulsion uses Tween80: Span80: OP-10 = 5:3:2 emulsifiers;

[0062] Emulsion B uses Tween80: Span80: EO-PO = 3:5:2 emulsifier compound;

[0063] The film-forming aid is ethylene glycol monobutyl ether: diethylene glycol butyl ether = 1:4;

[0064] The wetting agent is a silicone twin structure surfactant (TEGO-4100): polyether siloxane copolymer (TEGO-410) = 3:2;

[0065] The rust inhibitor is aluminum tripolyphosphate: zinc phosphate = 1:1.

[0066] The prepared water-based silicone coating was sprayed on the polished tinplate with a film thickness of 200 microns, placed in a high-temperature oven for cross-linking and curing, and after completion, taken out and cured for seven days before testing the application performance.

[0067] Comparative Example

[0068] A Teflon coating was selected as a comparative example for comparison.

[0069] The comparison coating sample was provided by Yangjiang Gangrong Co., Ltd. The sample is an oily Teflon coating, and the production process uses a spraying method with a film thickness of 200 microns.

[0070] The performance test results of Examples 1 to 3 and the comparative example are shown in Table 2.

[0071] Table 2 Performance test results

[0072]

[0073]

[0074] According to the performance test analysis of the three embodiments, it is found that the three schemes can meet the basic requirements of the coating. The results show that with the increase of the content of double bonds in the silicon-hydrogen bond and the vinyl group, the hardness of the generated film is improved under the action of nano-gas-phase silica. Under the same conditions, the hardness of the generated film increases with the increase of the MQ resin content. Therefore, under the action of a certain amount of nano-gas-phase silica, increasing the reaction group and increasing the content of the bulk resin are beneficial to improving the hardness of the generated film. According to the requirements of HG / T 4563, adhesion <0.1N / mm can be considered to achieve a non-stick effect. The embodiments of the present invention meet the requirements of the industry standard through the tape peeling force test.

[0075] In summary, the present invention has the following advantages:

[0076] 1. The present invention uses hydrogenated silicone oil, vinyl silicone oil and MQ resin as the base materials to achieve organic solvent-free, thus achieving environmental protection and pollution-free from the perspective of raw materials, reducing YOC emissions of coatings, and enhancing the safety of products in production, transportation and construction projects. It not only complies with the requirements of national laws and regulations, is environmentally friendly, safe and pollution-free, but also has excellent anti-corrosion, anti-stick and friction resistance.

[0077] 2. The coating provided by the present invention undergoes a slow addition reaction after spraying, and reacts under heating and the action of a catalyst to form an inorganic-organic polymer coating with a certain body structure with the participation of nano-scale fumed silica. No by-products are generated during the reaction process, and the raw materials are efficiently utilized.

[0078] 3. The coating of the present invention presents a three-dimensional network structure under an electron microscope. Compared with the two-dimensional network structure, it has excellent adhesion and has very outstanding advantages in terms of anti-sticking, wear resistance and anti-corrosion protection of metal materials.

[0079] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes are obvious to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The choice of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A safe, durable and anti-fouling blade, characterized in that: The safe, durable and antifouling blade has a safe, durable and antifouling coating on the surface of the blade substrate. The safe, durable and antifouling coating is a three-dimensional mesh structure. The safe, durable and antifouling coating is formed by polymerization of the following components: an aqueous electron donating pre-reaction composition; Aqueous electron-accepting pre-reacted monomer; Fumed silica; Adjuvants; and water.

2. The safe, durable and anti-fouling blade according to claim 1, characterized in that: The aqueous electron-donating pre-reaction composition comprises a first aqueous electron-donating pre-reaction monomer and a second aqueous electron-donating pre-reaction monomer; The first aqueous electron-donating pre-reaction monomer is one or more selected from MT silicone resin, MQ silicone resin, MDT silicone resin, and MTQ silicone resin; The second aqueous electron-donating pre-reaction monomer comprises vinyl silicone oil; The aqueous electron-accepting pre-reaction monomer includes hydrogen-containing silicone oil.

3. The safe, durable and anti-fouling blade according to claim 2, characterized in that: The vinyl content of the first aqueous electron-donating pre-reaction monomer is 0.09 to 0.10 mol / 100 g, 0.10 to 0.11 mol / 100 g, or 0.11 to 0.12 mol / 100 g; The vinyl content of the second aqueous electron-donating pre-reaction monomer is 0.02 to 0.05 mol / 100 g, 0.05 to 0.08 mol / 100 g, or 0.08 to 0.11 mol / 100 g; The hydrogen content of the aqueous electron-accepting pre-reaction monomer is 0.30-0.32%, 0.32-0.34%, 0.34-0.36%, 0.36-0.38% or 0.38-0.40%.

4. The safe, durable and anti-fouling blade according to claim 3, characterized in that: The components of the safe and durable antifouling coating include, by weight: 3 to 5 parts, 5 to 7 parts, 7 to 9 parts, 9 to 11 parts or 11 to 13 parts of the first aqueous electron-donating pre-reaction monomer; 28 to 30 parts, 30 to 32 parts, 32 to 34 parts, 34 to 36 parts or 36 to 38 parts of the second aqueous electron-donating pre-reaction monomer; 34-36 parts, 36-38 parts, 38-40 parts, 40-42 parts or 42-44 parts of the aqueous electron-accepting pre-reaction monomer; The weight fraction ratio of the aqueous electron accepting pre-reaction monomer composition to the aqueous electron donating pre-reaction monomer composition is 0.83-0.86, 0.86-0.89, 0.89-0.92, 0.92-0.95, 0.95-0.98, 0.98-1.01, 1.01-1.03, 1.03-1.05, 1.05-1.08, 1.08-1.11 or 1.11-1.

14.

5. The safe, durable and anti-fouling blade according to claim 3, characterized in that: The safe and durable antifouling coating is prepared by the following steps: S1: preparing an A emulsion containing the aqueous electron-accepting pre-reaction monomer, and preparing a B emulsion containing the first aqueous electron-donating pre-reaction monomer and the second aqueous electron-donating pre-reaction monomer; S2: uniformly mixing the A emulsion and the B emulsion and spraying the mixture onto the blade substrate; S3: The blade substrate is allowed to stand still and the polymerization reaction occurs to obtain the safe, durable and antifouling blade having the safe, durable and antifouling coating.

6. The safe, durable and anti-fouling blade according to claim 5, characterized in that: The A emulsion comprises hydrogen-containing silicone oil, fumed silica and a first emulsifier; the first emulsifier is a composite emulsifier comprising a nonionic and a polymer; The B emulsion includes vinyl silicone oil, MQ resin, a second emulsifier, a catalyst, a film-forming aid, a wetting agent and a rust inhibitor; the catalyst is a chloroplatinic acid catalyst; the film-forming aid is an alcohol ether compound; the film-forming aid includes ethylene glycol monobutyl ether and / or diethylene glycol butyl ether; the second emulsifier is a composite emulsifier including non-ionic and polymeric emulsifiers; the wetting agent is an organosilicon wetting agent; the rust inhibitor is one or two selected from aluminum tripolyphosphate and zinc phosphate.

7. The safe, durable and anti-fouling blade according to claim 5, characterized in that: The polymerization reaction temperature is 171-175° C., 175-179° C., 179-183° C., 183-187° C. or 187-191° C.; the polymerization reaction time is 10-12 min, 12-14 min, 14-16 min, 16-18 min or 18-20 min.

8. The safe, durable and anti-fouling blade according to claim 1, characterized in that: The auxiliary agents include emulsifiers, catalysts, film-forming auxiliary agents, wetting agents and rust removers.

9. A safe, durable and anti-fouling scissors, characterized in that: The scissors include any one of the safe, durable and anti-fouling blades as described in claims 1-8.

10. A safe, durable and anti-fouling utility knife, characterized in that: The utility knife comprises any one of the safe, durable and anti-fouling blades as described in claims 1-8.

Citation Information

Patent Citations

  • Stain-resistant putty spatula and manufacturing method thereof

    CN103967261A

  • Bi-component paper molding organic silicon emulsion and preparation method thereof

    CN118459993A

  • Blade of electric razor

    JP1995313748A

  • Low Coefficient of Friction Coating for Metallic Surfaces

    US20120034470A1

  • Film-forming silicone compositions having lubricating properties

    US4806430A

Cited By

  • Water-based organic silicon coating and preparation method thereof

    CN121022257A